Spatial and temporal clonal evolution during development of metastatic urothelial carcinoma. Issue 9 (17th August 2016) - Thomsen, Mathilde B.H.; Nordentoft, Iver; Lamy, Philippe; Høyer, Søren; Vang, Søren; Hedegaard, Jakob; Borre, Michael; Jensen, Jørgen B.; Ørntoft, Torben F.; Dyrskjøt, Lars
Abstract : Patients with metastatic bladder cancer have a median survival of only 13–14 months. Precision medicine using targeted therapy may improve survival. Here we investigated spatial and temporal tumour evolution and tumour heterogeneity in order to evaluate the potential use of targeted treatment of metastatic bladder cancer. We performed a proof‐of‐concept study by whole exome sequencing of multiple tumour regions (n = 22) from three patients with metastatic bladder cancer. DNA from primary and metastatic tumour biopsies was analysed for mutations using Mutect and potential therapeutic targets were identified. We identified 256, 265 and 378 somatic mutations per patient, encompassing mutations with an estimated functional impact in 6–12 known disease driver genes per patient. Disease driver mutations present in all tumour regions could be identified in all cases, however, over time metastasis specific driver mutations emerged. For each patient we identified 6–10 potentially therapeutic targets, however very few targets were present in all regions. Low mutational allele frequencies were observed in most regions suggesting a complex mixture of different cancer cells with no spatial demarcation of subclones. In conclusion, primary bladder tumours and metastatic lesions showed heterogeneity at the molecular level, but within the primary tumour the heterogeneity appeared low. The observed lack of potential therapeutic targets common to all cancer cells in primary tumours and metastases emphasizes the challenges in designing rational targeted therapy solely based on analysis of the primary tumours. Highlights: Low intra‐tumour genetic diversity in primary tumour. High genetic diversity between primary tumours and metastatic lesions. Few potential therapeutic targets appear shared by all tumour cells. APOBEC‐related mutagenesis observed in aggressive primary tumours.